Clinical significance of cerebral microbleeds on MRI: A comprehensive meta-analysis of risk of intracerebral hemorrhage, ischemic stroke, mortality, and dementia in cohort studies (v1). Issue 5 (July 2018) - Charidimou, Andreas; Shams, Sara; Romero, Jose R; Ding, Jie; Veltkamp, Roland; Horstmann, Solveig; Eiriksdottir, Gudny; van Buchem, Mark A; Gudnason, Vilmundur; Himali, Jayandra J; Gurol, M Edip; Viswanathan, Anand; et al.
Background: Cerebral microbleeds can confer a high risk of intracerebral hemorrhage, ischemic stroke, death and dementia, but estimated risks remain imprecise and often conflicting. We investigated the association between cerebral microbleeds presence and these outcomes in a large meta-analysis of all published cohorts including: ischemic stroke/TIA, memory clinic, "high risk" elderly populations, and healthy individuals in population-based studies. Methods: Cohorts (with > 100 participants) that assessed cerebral microbleeds presence on MRI, with subsequent follow-up (≥3 months) were identified. The association between cerebral microbleeds and each of the outcomes (ischemic stroke, intracerebral hemorrhage, death, and dementia) was quantified using random effects models of (a) unadjusted crude odds ratios and (b) covariate-adjusted hazard rations. Results: We identified 31 cohorts ( n  = 20, 368): 19 ischemic stroke/TIA ( n  = 7672), 4 memory clinic ( n  = 1957), 3 high risk elderly ( n  = 1458) and 5 population-based cohorts ( n  = 11, 722). Cerebral microbleeds were associated with an increased risk of ischemic stroke (OR: 2.14; 95% CI: 1.58–2.89 and adj-HR: 2.09; 95% CI: 1.71–2.57), but the relative increase in future intracerebral hemorrhage risk was greater (OR: 4.65; 95% CI: 2.68–8.08 and adj-HR: 3.93; 95% CI: 2.71–5.69). Cerebral microbleeds were an independent predictor of all-cause mortality (adj-HR: 1.36; 95% CI: 1.24–1.48). In three population-based studies, cerebral microbleeds were independently associated with incident dementia (adj-HR: 1.35; 95% CI: 1.00–1.82). Results were overall consistent in analyses stratified by different populations, but with different degrees of heterogeneity. Conclusions: Our meta-analysis shows that cerebral microbleeds predict an increased risk of stroke, death, and dementia and provides up-to-date effect sizes across different clinical settings. These pooled estimates can inform clinical decisions and trials, further supporting cerebral microbleeds role as biomarkers of underlying subclinical brain pathology in research and clinical settings.